Multi-objective layered diagnosis model of electric power ICT network based on extenics - Li LI; Tiantian LUO; Yana ZHANG; Runze WU (Dianxin kexue)
Electric power ICT network is an important part of power system,which plays a vital role in the security,stability and economic operation of power network.A diagnostic index system of electric power ICT network was established and a multi-objective layered diagnosis model of electric power ICT network system based on extension rating was proposed.This evaluation method could not only evaluate the impact factors of the electric power ICT network,but also diagnose and rate the whole electric power ICT network.